Frequency of anti-glycoprotein Ia/IIa (anti-HPA-5b,-5a) and anti-glycoprotein IIb/IIIa (anti-HPA-1a,-3a,-4a) alloantibodies in multiparous women of African descent - Zaccheaus A Jeremiah; Justina E Oburu; Osaro Erhabor; et al (Dove Medical Press, 2010)
Zaccheaus A Jeremiah1, Justina E Oburu2, Osaro Erhabor1, Fiekumo I Buseri1, Teddy C Adias31Haematology and Blood Transfusion Science Unit, Department of Medical Laboratory Sciences, College of Health Sciences, Niger Delta University, Wilberforce Island, Nigeria; 2Department of Haematology and Blood Transfusion, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria; 3Rivers State University of Science and Technology, Port Harcourt, NigeriaBackground: Human platelet antibodies are often implicated in some disease conditions, such as neonatal alloimmune thrombocytopenia (NAIT), idiopathic thrombocytopenic purpura (ITP) and platelet refractoriness. The frequencies of these alloantibodies have not been reported in Nigeria and West Africa.Methods: Screening for allontibodies to human platelet antigens (HPA) was undertaken using the GTI PakPlus® qualitative solid phase ELISA reagent. Platelet count was done using the ICSH approved procedure using 1% ammonium oxalate reagent.Study design: A cross-section of apparently healthy adult Nigerian multiparous non-pregnant women, who were staff of a tertiary health facility in the Niger Delta, Nigeria, were screened for alloantibodies to human platelet antigens.Results: Of the one hundred (100) women screened, the prevalence of anti-glycoprotein IIb/IIIa (anti-HPA-Ia,-3a,-4a) was zero percent (0%), anti-glycoprotein Ia/IIa (anti-HPA-5b) accounted for 30% of results, while anti-glycoprotein Ia/IIa (anti-HPA-5a) was 18%. Parity was found to exert significant influence on the development to HPA antibodies (Fisher’s Exact Test = 11.683, P < 0.05; 13.577, P < 0.01). The platelet count of the women did not appear to exert any influence on the development of the antibodies (P > 0.05).Conclusion: This study has observed a high prevalence of anti-HPA-5b in our sample population. The prevalence of alloantibodies to HPA antigens was found to associate strongly with parity. These results indicate that there is a need to initiate platelet serology in our tertiary health institutions, as well as educate our women on the risk associated with frequent pregnancies, and ensure that adequate caution is taken when recruiting multiparous women as blood donors.Keywords: Nigeria, multiparous, blood donor, platelet serology, platelet count